PENGARUH SEGMENTING, TARGETING DAN POSITIONING TERHADAP EFEKTIVITAS STRATEGI PEMASARAN PADA ENCAR DAIHATSU CABANG BATURAJA - Yuniarti Anwar; Harby Wiralaga; Aditia Putra Santoso (KOLEGIAL, 2022)
The purpose of this study was to determine the effect of segmenting, targeting and positioning on theeffectiveness of the marketing strategy at Encar Daihatsu Baturaja Branch. This research uses descriptiveresearch method. The results of the research and discussion obtained multiple linear regression asfollows: Y = 0.395 + 0.409 X1 + 0.114 X2 + 0.427 X3. The correlation coefficient value of 0.817 based onthe correlation coefficient interval can be stated that the relationship between segmenting (X1), targeting(X2) and positioning (X3) variables on the effectiveness of marketing strategy (Y) is strong, because it is inthe interval 0.60-0.799. Testing the hypothesis that produces a calculated t value for the segmentingvariable is (1.415) < t table (2.17881) this means that Ho is accepted and Ha is rejected, meaning thatthere is no effect of segmenting on the effectiveness of the marketing strategy at Encar Daihatsu BaturajaBranch. The calculated t value of the targeting variable is (0.498) <t table (2.17881) this means that Ho isaccepted and Ha is rejected, meaning that there is no effect of targeting on the effectiveness of themarketing strategy at Encar Daihatsu, Baturaja Branch. The t value of the positioning variable is (1.708) <ttable (2.17881) this means that Ho is accepted and Ha is rejected, meaning that there is no positioningeffect on the effectiveness of the marketing strategy at Encar Daihatsu, Baturaja Branch. While the resultsof the F test obtained the value of Fcount (3.315) < Ftable (3.49) means rejecting Ha and accepting Ho.Thus segmenting (X1), targeting (X2), positioning (X3) simultaneously does not affect the effectiveness ofthe marketing strategy at Encar Daihatsu Baturaja Branch (Y).